PERKEMBANGAN LINGKUNGAN PENGENDAPAN DARI FORMASI SAMBIPITU KE FORMASI WONOSARI DAERAH JELOK, DESA BEJI, KECAMATAN PATOK, KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Tania, Dina (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
The research is investigating Middle Miocene to Pliocene geological stage of sediment depositional changing in Dusun Beji, Desa Jelok, Kecamatan Patuk, Kabupaten Gunung Kidul, Special Regionof Yogyakarta. Base on the measure section of cross-section analysis and bentonitic fossil analysis, the research area has three formations from old to young formation such as Sambipitu Formation, Oyo Formation, and Wonosari Formation. The result analyzed that microfossil show Sambipitu Formation deposition in the middle of the neritic zone and changedintothe deep neritic zone until lower bathyal in Oyo Formation, and it changes become more shallow in Wonosari Formation, which is depositions in the lower neritic zone to upper neritic zone as long Middle Miocene to Pliocene age. Sambipitu and Oyo Formation havedepositional changing from Lower Fan to Supra Fan Lobes on Mid Fan with lithology change form silt with bioturbation structure to pumice breccia, tuff, sandstone and claystone with slump structure, lamination and massive. In other depositional in Wonosari Formation have environment of Inner Ramp with clastic limestone dominated such as calsirusite and calcarenite.